A Common Value Experimentation with Multiarmed Bandits. (30th July 2018) - Gao, Xiujuan; Liang, Hao; Wang, Tong
Abstract : We study a value common experimentation with multiarmed bandits and give an application about the experimentation. The second derivative of value functions at cutoffs is investigated when an agent switches action with multiarmed bandits. If consumers have identical preference which is unknown and purchase products from only two sellers among multiple sellers, we obtain the necessary and sufficient conditions about the common experimentation. The Markov perfect equilibrium and the socially effective allocation in K -armed markets are discussed.